PENGARUH PEMBERIAN PENGHARGAAN TERHADAP KINERJA PEGAWAI DI DINAS KEBUDAYAAN DAN PEMUDA KABUPATEN ACEH BARAT - Mursyidin Mursyidin (Universitas Teuku Umar, 2017)
The awarding of employee service, aiming to motivate the passion and loyalty. The award, a government effort to provide remuneration or the work of employees, so as to encourage employees to be more enterprising and achievement. The award was in recognition of an achievement that has been achieved by a person, who will be a strong motivator. While the performance of employees, is the result of work achieved in executing the duties or responsibilities assigned to them, which are based on the timeliness, quality work. In this study, the authors use quantitative data analysis, namely data processing in the form of numbers, whether as a result of measurement and results. Kompensi, more widely used in research because it produces a more precise conclusion, compared with qualitative analysis techniques. Based on the results of research conducted, the results of coefficient r = 0.574 and r rithmetic tables 0.266 (0.574> 0.266), it can be concluded that there is a positive relationship between the awarding of the performance of employees, the Department of Education Culture Youth and Sports. From the table data classification determines that the award in the cultural education offices Youth and Sports, at the high category. This shows that the award to the Department of Education Culture Youth and Sport has been good, while for the result of the impact of the award on employee performance is pa6da very high category. Researchers found that employees expect every year, Head of promoting employee or proposed employee in order to get the award. Given to every employee job performance, will improve the performance of the duties in their respective fields.Keywords: awards, performance, employee